Feasibility of molecular testing in a multicenter study with geographical variation in India: Epidermal growth factor receptor mutation as a model molecular test - Prabhash, Kumar; Rauthan, Amit; Rajappa, Senthil; Desai, Chirag; Mistry, Rajesh; Dutt, Amit; Chougule, Anuradha; Mohan, Ravi; Das, Pratap; Kumar, Rajiv; Noronha, Vanita; Joshi, Amit; et al. (Asian journal of oncology, 2017)
Context: Trends in epidermal growth factor receptor (EGFR) mutation based on ethnicity assist the initial selection of targeted therapy regimen. Reported incidence of EGFR mutation in Indian NSCLC patients is variable, ranging from 22% to 51.8%. Aim and Settings and Design: This multicenter, noninterventional study evaluated the prevalence of EGFR mutation in Indian NSCLC patients, its association with patients’ demographics, and for the first time used a central laboratory for molecular testing. Subjects and Methods: Tissue samples from 252 NSCLC patients were tested at a Central Laboratory at Tata Memorial Hospital. Statistical Analysis Used: Patient demographics, baseline characteristics including smoking status from routine examination were recorded in a single visit. Chi-square or Fisher's exact test was used for association of EGFR mutation status with gender, age, smoking status, and histological subtypes. Results: The prevalence of EGFR mutation in Indian NSCLC patients was 23.4%. Among these, 55.9% patients had mutations in exon 19, 39% in exon 21, and 1.7% in exon 18. The incidence of EGFR mutation was higher in females than males (32.5% vs. 18.9%, respectively), and in 30.6% patients that had never smoked, 26.3% smokers, and 5.8% former smokers. The mean duration of transportation of tissue samples to the central laboratory was 48 h with an average turnaround time of 5 days for molecular testing. Conclusions: Molecular testing at a central laboratory is a feasible option in India. Prevalence of EGFR mutation in Indian NSCLC patients was similar across western and southern centers in India. A statistically significant association between EGFR mutation and gender as well as the smoking status of the patients was observed. Majority of the patients had in-frame deletions in exon 19.